Parental attitude and Instagram addiction: The mediating role of obsessive-compulsive disorder - Avcı, Ümmühan; Karaoğlan Yılmaz, Fatma Gizem; Yılmaz, Ramazan; Yılmaz, Ramazan; Avcı, Ümmühan; Karaoğlan Yılmaz, Fatma Gizem (Wiley, 2023)
The study examined the relationship between democratic, authoritarian, and protective-demanding parental attitudes, obsessive-compulsive disorder (OCD), and Instagram addiction. It is based on the correlational research design in which the structural relationships between the variables were used. The study was carried out on 421 university students using Instagram. Of the students participating in the study, 233 were females (55.3%), and 188 were males (44.7%). Parental attitude scale, Instagram addiction scale, and OCD scale were used for the data collection, and Structural Equation Modeling was used for the data analysis. According to the study results, protective/demanding parental attitude significantly predicts OCD, OCD significantly indicates Instagram addiction, and OCD mediates the relationship between protective/demanding parental attitude and Instagram addiction. Conversely, democratic parental attitude does not predict OCD, and authoritarian parental attitude does not predict OCD. Based on the results of this study, protective/demanding parental involvement should be considered when preparing a strategic move to reduce OCD and prevent Instagram addiction among young people. In this a mediation model, the focus of intervention is OCD. Therefore, based on the results of this study, OCD should be considered when preparing a strategic move to prevent or treat Instagram addiction among young people.
Keywords: Instagram Addiction; Obsessive-Compulsive Disorder; Parental Attitude; Structural Equation Modeling; University Students